2008
DOI: 10.1002/adma.200701479
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Ionic Impurities in Poly(vinyl alcohol) Gate Dielectric: Possible Source of the Hysteresis in Organic Field‐Effect Transistors

Abstract: Ionic impurities in gate dielectrics are outlined as a possible source for threshold voltage shifts in organic field effect transistors. Using poly(vinyl alcohol) containing sodium acetate impurities we show how transistors can be designed for memory elements or polymer integrated circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 35 publications
4
71
2
Order By: Relevance
“…Their presence confirms that the memory effect is driven by ferroelectric polarization switching, rather than charge trapping mechanisms or ion migration in and through the ferroelectric layer. 20,21 Hence, the transistor behaves as a bi-stable memory cell element; before the very first sweep, the ferroelectric film is unpolarized. Upon increasing the negative gate bias beyond the coercive Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Their presence confirms that the memory effect is driven by ferroelectric polarization switching, rather than charge trapping mechanisms or ion migration in and through the ferroelectric layer. 20,21 Hence, the transistor behaves as a bi-stable memory cell element; before the very first sweep, the ferroelectric film is unpolarized. Upon increasing the negative gate bias beyond the coercive Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…In the final step, the material was washed copiously with deionized water (18 MV Â cm) and dried over night in a vacuum oven at 60 8C. It turned out that cleaning was the most important issue in the fabrication of working transistors, as also observed in solution based processing [41] . Samples were collected from the dried powder and evaporated under a high vacuum ( p < 5 Â 10 À6 bar).…”
Section: Methodsmentioning
confidence: 99%
“…M. Egginger et al concluded that the change in the volume charge distribution within PVA gate dielectric as well as the variation in the charge distribution at organic semiconductor/dielectric interface affect the hysteresis by the field induced polarization of dielectric. 17 The theoretic simulations of charge transport in the dielectric of OFETs were made by E. Orgiu et al 18 The simulations confirmed the experiment data, which showed that the charge transports in the dielectric was responsible for the hysteresis. Meanwhile, many researches have been carried out to avoid the hysteresis of PVA.…”
mentioning
confidence: 80%
“…circumstance of PVA dielectric, the charge transport in PVA bulk and the charge trapping/detrapping process in PVA bulk and/or at the interface of organic semiconductor/PVA are considered to be the origin of hysteresis. [16][17][18] Also, the electrical characteristic of device A varies significantly as the multi-test of device, which further verifies charge traps in PVA bulk or at the interface of PVA/pentacene. 23 Device B based on single PMMA (620 nm) exhibits almost no hysteresis in the transfer curve.…”
mentioning
confidence: 86%